PENERAPAN PENDEKATAN SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY (SETS) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 1 UJUNGBATU - Ratna Kusumawardani; Herdini '; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The research about approach science, environment, technology and society (SETS) in SMA Negeri 1 Ujungbatu has done. The aim of this research is to improve student achievement on the subject of the atomic structure and elements of the periodic system in class X Senior High School 1 Ujungbatu. The research used an experimental method using randomized control group pretest-posttest design. The Sample consists of 2 classes, X2 as an experiment class (applied approach SETS) and X5 as the control class (without approach SETS). Data analysis technique used t-test. Based on test data analysis obtained tcount>ttable is 6,76>1,67, meaning that the use of approach SETS can increase student achievement on the subject of the atomic structure and elements of the periodic system in class X Senior High School 1 Ujungbatu. The increasing of student learning achievment category (N-Gain) is high 0.71.Key words:Learning Achievement, Approach SETS, The Atomic Structure and Elements of the Periodic System